PENGARUH DUKUNGAN KELUARGA TERHADAP KEPATUHAN DIET PADA PASIEN DIABETES MELLITUS DI RUMAH SAKIT PEKANBARU - Roni, Yunisman; Lestari, Rizky Dwi; Khusniyati, Nia (Coping: Community of Publishing in Nursing; Vol 12 No 2 (2024): April 2024DO - 10.24843/coping.2024.v12.i02.p07, 2024)
The four pillars in the management and prevention of diabetes mellitus are education, medical nutrition therapy, physical exercise, and pharmacological intervention. The goal of the diet is to prevent complications of diabetes mellitus, but dietary challenges represent a significant obstacle to achieving a better quality of life. Dietary adherence can be influenced by family support, as family provides motivation, full support, and care. The aim of this study was to determine the effect of family support on dietary compliance in diabetes mellitus patients. The research method used was quantitative research with a cross sectional design involving 60 respondents selected by purposive sampling at a Pekanbaru Hospital. Data collection used the HDFSS questionnaire for family support and PDAQ for adherence diet. The results of the study showed that 63,3% of respondents had low family support and 73,3% of respondents had low DM diet adherence so that there was a strong influence between family support and diet compliance in diabetes mellitus patients with a p-value of 0,000. DM patient diet compliance will be higher if family support is higher, but vice versa. The conclusion in this study is that there is a strong influence of family support on dietary compliance in diabetes mellitus patients.